EXPERIMENTAL PERMEABLE ASPHALT PAVEMENT USING LOCAL MATERIAL DOMATO STONE ON QUALITY OF POROUS ASPHALT - Chairuddin, Firdaus; Tjaronge, Wihardi; Ramli, Muhammad; Patanduk, Johannes (Jurnal Teknik Sipil, 2018)
Abstract: The lot deposit of Domato Stone as local material from sea location in Banggai island in half Sulawesi of Indonesia. Was still not be exploited better. Some research in the field of road construction showed that Domato Stone was powerful enough when mixture asphalt structure. Permeable asphalt pavement or porous friction course is commonly known as porous asphalt. The porous pavement used in Japan and Europe. The pavement consists in a porous overlay allowing rainwater to flow down to the bottom the overlay and then to drain on the edges of the pavement. Quality of porous asphalt was developed to drain pavement surface flow through its pores, because of is specific properties to measure its ability to drain the water ( Permeability ), a special measur-ing device is required. This study is aimed to measure the coefficient of permeability using the constant head permeability test at transportation laboratory Hasanuddin University. The result was compared with the previous study. The test included horizontal and vertical permeability. Their types of gradation were incorporated to: British Graduation, Binamarga Gradation, and Australian Gradation. The tests were carried out at optimum bitumen content, the result shows that the verti-cal permeability of porous asphalt using British Gradation were: 0,0914, 0,2841 and 0,2912 Cm/sec. Respectively meanwhile for horizontal permeability were 0,1168, 03212, 0,2897 Cm/Sec. The Marshall stabilities were at on contrary to the permeabilities, the porosity was comparable to the permeabilities. The results of researches indicate that porous asphalt mixture showed an influ-ence on the value of the characteristics of porous asphalt particularly at concrete waste fraction grading 50% retained 1/2 " and 50% natural crushed stone retained 3/8" where the values obtained from the analysis of optimum binder content is 9.5%. Based on the Scanning Electron Microscope (SEM) can be seen the microstructure and content of chemical elements present in the porous as-phalt which prove that all elements of the liquid asbuton and concrete waste can blend and bind well.